2016
DOI: 10.1016/j.plaphy.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of a barley (Hordeum vulgare) leucine-rich repeat, non-arginine-aspartate receptor-like protein kinase reduces expression of numerous genes involved in plant pathogen defense

Abstract: Pattern recognition receptors represent a first line of plant defense against pathogens. Comparing the flag leaf transcriptomes of barley (Hordeum vulgare L.) near-isogenic lines varying in the allelic state of a locus controlling senescence, we have previously identified a leucine-rich repeat receptor-like protein kinase gene (LRR-RLK; GenBank accession: AK249842), which was strongly upregulated in leaves of early-as compared to late-senescing germplasm. Bioinformatic analysis indicated that this gene codes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 76 publications
(114 reference statements)
0
7
0
Order By: Relevance
“…RLKs were categorized into RD kinases and non-RD kinases according to the RD motif in their kinase domains [70]. By far, well-studied LRR-RLK PRRs, such as FLS2 or Xa21 [71, 72], that recognize the exogenous PAMPs in disease resistance were non-RD kinases [70]. Characterized plant DAMP receptors all contained RD kinase domains [4].…”
Section: Discussionmentioning
confidence: 99%
“…RLKs were categorized into RD kinases and non-RD kinases according to the RD motif in their kinase domains [70]. By far, well-studied LRR-RLK PRRs, such as FLS2 or Xa21 [71, 72], that recognize the exogenous PAMPs in disease resistance were non-RD kinases [70]. Characterized plant DAMP receptors all contained RD kinase domains [4].…”
Section: Discussionmentioning
confidence: 99%
“…A possible candidate gene is HORVU3Hr1G067050 which expresses leucine-rich repeat (LRR) receptor-like protein kinase family protein. LRR receptor-like protein kinase is a type of cell surface receptors represented by receptor(-like) kinases (RKs, RLKs), which consists of extracellular receptor, transmembrane and intracellular protein kinase domains 40 and is involved in plant pathogen defence 41 . Ryd2 not only confers field tolerance as observed in this study, it has also been reported to be capable of reducing virus titre in young plants infected with BYDV-PAV or BYDV-MAV 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…hordei ) and stem rust ( Puccinia graminis f. sp. tritici ) resulted in reduced defense genes expression, suggesting a tentative PRR role against these fungal pathogens ( Parrott et al, 2016 ). TaLRRK-6D and HvLRRK-6H add a cereal gene to the list of LRR-RLK sub-family LRR XII genes with proven roles in defense against pathogens; this sub-family also includes Arabidopsis FLS2, Arabidopsis EF-Tu receptor and rice Xa21 ( Shiu et al, 2004 ; Schoonbeek et al, 2015 ; Schwessinger et al, 2015 ; Thomas et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%